Electrode patch for resisting sebum pollution in sweat detection and wearable electrochemical sensor
By using super-hydrophilic MOFs electrodes to directly contact the skin, the sensor performance passivation problem caused by sebum contamination in sweat detection is solved, and a sweat sensor with high sensitivity, rapid response and long-term stability is achieved.
Patent Information
- Application Number
- CN202510085365.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During sweat detection, due to biological contamination of sebum, sebum accumulates in the electrode surface area, causing problems such as blocking of the sensing path, decreasing current signal, and passivation of sensor performance.
The ultra-hydrophilic metal organic frame (MOFs) sensing electrode was prepared by spraying the MOFs precursor solution and in-situ self-assembly process, combined with magnetron sputtering process and coating of Ag/AgCl suspension, a direct contact MOFs electrode patch was prepared.
It realizes effective resistance to sebum, maintains the high sensitivity, rapid response and long-term stability of the sensor, and solves the problem of sensor performance passivation caused by sebum contamination.
Smart Images

Figure CN119523477A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sweat detection, and in particular to an electrode patch and a wearable electrochemical sensor for resisting sebum contamination in sweat detection. Background Art
[0002] Wearable electrochemical sweat sensors can be attached to the surface of human skin to achieve real-time and continuous monitoring of individual biochemical indicators without interfering with individual behavior. In sweat detection, biological contamination caused by sebum is a common and often overlooked problem. Sebum secreted by sebaceous glands and sweat secreted by sweat glands mix on the surface of the skin and are simultaneously transported to the sensor surface. As the detection time increases, a large amount of sebum will inevitably accumulate on the electrode surface, causing problems such as blocking of the sensing pathway, decreased current signal, and passivation of sensor performance.
[0003] Current technical means usually use physical barrier methods to filter sebum, or coat a layer of Nafion membrane on the surface of the sensing electrode to block the contact between sebum and the sensing electrode. These methods eliminate the interference of sebum by indirect means, which usually affects the direct contact between the electrode and sweat, accompanied by reduced electrode sensitivity and slower response speed. At present, there is an urgent need for a direct contact anti-sebum interference strategy to simultaneously meet the requirements of sensor sensitivity, rapid responsiveness and durability. Metal-organic frameworks (MOFs) have become an emerging electrochemical sensor electrode material due to their rich catalytic active sites, large surface area and tunable structural characteristics. By designing the structure and regulating the chemical composition of MOFs, it is expected to solve the problem of sebum adhesion on the electrode surface, thereby stabilizing the performance of the sensor. Summary of the invention
[0004] In order to solve the problem of sweat detection electrode contamination and performance passivation caused by sebum on the skin surface, the present invention provides an electrode patch and a wearable electrochemical sensor for resisting sebum contamination in sweat detection, thereby improving the sensitivity, response speed and stability of the sensor.
[0005] An electrode patch for resisting sebum pollution in sweat detection comprises a working electrode, an Ag / AgCl@PVB reference electrode, an Au counter electrode and a flexible polyimide substrate. The working electrode is a superhydrophilic MOFs sensing electrode, and the MOFs sensing electrode is prepared from any one MOFs precursor material of Cu-HHTP, Ni-HHTP and Cu-THQ.
[0006] Furthermore, the MOFs sensing electrode is prepared by spraying a MOFs precursor solution and an in-situ self-assembly process; the spraying method of the MOFs precursor solution includes any one of inkjet printing, dispensing, and drip coating; the temperature of the in-situ self-assembly process is 50-85°C and the time is 0.5-3h.
[0007] Furthermore, the Au counter electrode is prepared by a magnetron sputtering process, and the Ag / AgCl@PVB reference electrode is prepared by coating an Ag / AgCl suspension and dripping a PVB mixed solution; wherein the PVB mixed solution includes PVB, NaCl, F127 and methanol.
[0008] Based on the above-mentioned electrode patch for resisting sebum contamination in sweat detection, the present invention also provides a wearable electrochemical sensor, which also includes a microfluidic sweat collection channel, and the microfluidic sweat collection channel is in direct contact with the electrode patch.
[0009] Furthermore, the microfluidic sweat collection channel includes a PDMS microfluidic chip, and the PDMS microfluidic chip includes a plurality of sweat inlets, a sweat storage area and a sweat outlet.
[0010] Furthermore, the PDMS microfluidic chip also includes an electrical stimulation gel, which includes an anode gel and a cathode gel, wherein the anode gel is prepared from agarose and carbachol, and the cathode gel is prepared from agarose and NaCl.
[0011] Furthermore, the electrochemical sensor also includes a PI film substrate, a flexible printed circuit board and an APP software client.
[0012] Preferably, the electrochemical sensor is integrated by an electrode patch, a PI film substrate, a microfluidic sweat collection channel, a flexible printed circuit board and an APP software client, wherein the electrode patch is located between the PI film substrate and the microfluidic sweat collection channel, and the microfluidic sweat collection channel is located on the flexible printed circuit board.
[0013] Furthermore, the preparation of the PDMS microfluidic chip includes a photolithography process and a PDMS chip mold reversing process. The photoresist used in the photolithography process is SU-8, the coating speed is 1800-2200 rpm, the coating time is 30-45 s, and the thickness of the obtained photoresist layer is about 100-120 um.
[0014] Furthermore, the photolithography process also includes an exposure process and a development process, and the exposure dose in the exposure process is 230-250 mj / cm 2, the baking temperature is 85-100°C; the developing time of the developing process is 7-10min, and the baking temperature is 130-140°C.
[0015] The advantages of the present invention are: The present invention provides an electrode patch and a wearable sensor for resisting sebum pollution in sweat detection, proposes a direct contact anti-sebum pollution electrode construction strategy, and prepares a MOFs sensing electrode with super hydrophilicity and underwater oleophobicity by regulating the structure, chemical composition, and surface physicochemical properties of MOFs materials. The MOFs sensing electrode has no diaphragm on its surface and is in direct contact with a microfluidic sweat collection channel. Compared with the prior art, this direct contact anti-sebum pollution super hydrophilic MOFs sensing electrode construction strategy can solve the problems of sweat detection electrode pollution and performance passivation caused by sebum on the skin surface, and provides a novel method for realizing a wearable sweat sensor with high sensitivity, rapid response, high accuracy, and long-term durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A schematic diagram of an electrode patch based on a MOFs electrode provided in Example 1 that has the function of resisting interference from sebum in sweat; Figure 2 Schematic diagram of the structure of different hydrophilic MOFs sensing electrodes in Examples 1-5; Figure 3 The water contact angle and underwater oil contact angle test diagram of different hydrophilic MOFs sensor electrodes in Test Example 1; Figure 4 The sebum adhesion on the surface of the sensing electrode of MOFs with different hydrophilicity in test example 2; Figure 5 The changes of electrochemical signals of MOFs sensing electrodes with different hydrophilicity under the interference of sebum in test example 3; Figure 6 To test the ability of the sensor prepared by the different hydrophilic MOFs sensing electrodes in Example 4 to monitor the UA level in human sweat in real time for a long time; Figure 1 Reference numerals: 1. PI film base; 2. Electrode patch; 21. Working electrode; 22. Reference electrode; 23. Counter electrode; 3. Microfluidic sweat collection channel; 31. Electrical stimulation gel; 32. Sweat inlet; 33. Sweat storage area; 34. Sweat outlet; 4. Flexible printed circuit board; 5. APP software client. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.
[0018] It should be noted that the various installation methods and technical terms mentioned in the invention are technical terms that have long been clearly known in the relevant technical field, so no further explanation is given. In addition, the same reference numerals are used for the same components, but this does not affect and should not constitute an accurate understanding of the technical solution by those skilled in the art.
[0019] Embodiment 1 This embodiment provides a wearable electrochemical sensor for resisting sebum contamination in sweat detection, such as Figure 1 As shown, it is integrated by a PI film base layer 1, an electrode patch 2 for resisting sebum contamination in sweat detection, a microfluidic sweat collection channel 3, a flexible printed circuit board 4 and an APP software client 5; wherein the electrode patch 2 for resisting sebum contamination in sweat detection is located between the PI film base layer 1 and the microfluidic sweat collection channel 3, and the microfluidic sweat collection channel 3 is located on the flexible printed circuit board 4.
[0020] The electrode patch 2 for resisting sebum contamination in sweat detection includes a working electrode 21 (the working electrode of this embodiment is a Cu-HHTP electrode), a reference electrode 22 (the reference electrode of this embodiment is Ag / AgCl@PVB), a counter electrode 23 (the counter electrode of this embodiment is a gold electrode) and a substrate (the substrate of this embodiment is a flexible polyimide). The specific preparation process is as follows: Step 1: Preparation of substrate: The PI film was fixed on the surface of the silicon substrate and washed with a mixture of ethanol and hydrogen peroxide to obtain a PI flexible substrate; Step 2: Preparation of the electrode 23: Cover the electrode mask on the PI flexible substrate obtained in step 1, use Au as the target source, perform magnetron sputtering for 120 s at a voltage of 25 mV, and then remove the mask to obtain a 50 nm thick Au circuit thin layer as a conductive layer (gold layer) and a gold counter electrode; Step 3: Preparation of reference electrode 22: Apply the commercial Ag / AgCl suspension to the gold counter electrode obtained in step 2, dry naturally in the dark to obtain the Ag / AgCl electrode, weigh 79.1 mg PVB, 50 mg NaCl, 1 mg F127, add 1 mL methanol, and ultrasonically disperse to prepare a PVB mixed solution; take 3 μL of the PVB mixed solution and drop it on the Ag / AgCl electrode, and after drying, the Ag / AgCl@PVB reference electrode is obtained.
[0021] Step 4: Preparation of working electrode 21: Step 4-1, HHTP (0.023 mmol) and Cu(NO3)2·3H2O (0.02 mmol) were dissolved in 4 mL of a mixed solution (DMF: water = 1:7), and the Cu-HHTP precursor solution was obtained after ultrasonic treatment for 10 minutes; Step 4-2: Use inkjet printing technology to spray the Cu-HHTP precursor solution obtained in step 4-1 onto the gold layer, place it in an oven at 60°C for in-situ growth for 1 hour, wash it with water and acetone in turn, and then dry it to obtain a Cu-HHTP electrode (structure as shown in FIG. Figure 2 as shown).
[0022] The microfluidic sweat collection channel 3 comprises a PDMS microfluidic chip, and the PDMS microfluidic chip comprises an electrical stimulation gel 31 , a plurality of sweat inlets 32 , a sweat storage area 33 and a sweat outlet 34 .
[0023] The specific preparation process of the microfluidic sweat collection channel 3 is as follows: (1) Use acetone solution to ultrasonically clean the silicon wafer. After cleaning, heat the silicon wafer in an oven at 120°C for 15 minutes to eliminate surface moisture and make SU-8 better adhere to the substrate; (2) Use plasma treatment for 2 minutes to increase the uniformity of photoresist distribution and reduce the formation of holes; (3) Use a coating machine to evenly spin-coat a small amount of SU-8 photoresist on the substrate at a coating speed of 2000 rpm and a coating time of 30 s to ensure that the thickness of the photoresist layer is about 110 um. Then, use a hot plate to bake the SU-8 photoresist at 95 °C for 20 min. (4) At an exposure dose of 240 mj / cm 2 The designed pattern was imported into the photolithography software for photolithography, and then the SU-8 photoresist was baked on a hot plate at 95°C for 8 minutes; (5) Diluting the uncross-linked SU-8 photoresist in a solvent to present the channel design pattern of the chip on the substrate, and developing the SU-8 photoresist with a developer. After 10 minutes, heating the SU-8 photoresist at 135°C can suppress the residual strength in the glue layer, causing some cracks in the glue layer to disappear and become harder; (6) After mixing the polydimethylsiloxane (PDMS) main agent and the hardener in a ratio of 10:1 and removing the bubbles, slowly pour it onto the SU-8 microchannel pattern and heat it at 60°C for hardening. After the PDMS is completely solidified, carefully remove it from the SU-8 mold to obtain the microfluidic sweat collection channel 3.
[0024] The electrical stimulation gel 31 includes an anode gel and a cathode gel, and the specific preparation process is as follows: Preparation of anode gel: Agarose was dissolved in deionized water at 100°C to prepare a solution with a concentration of 3% (w / w). Then, carbachol was added to the polymer solution and stirred evenly to fully dissolve the carbachol in the solution to prepare a carbachol solution with a concentration of 1% (w / w). After the solution was cooled to room temperature, it was slowly poured into the pre-prepared microfluidic patch and allowed to stand at 4°C for 10 minutes to obtain the anode gel.
[0025] Preparation of cathode gel: Agarose was dissolved in deionized water at 100°C to prepare a 3% (w / w) solution. Then, NaCl was added to the polymer solution and stirred evenly to prepare a 1% (w / w) NaCl solution. After the solution was cooled to room temperature, it was slowly poured into the pre-prepared microfluidic patch and allowed to stand at 4°C for 10 minutes to obtain cathode gel.
[0026] Example 2 This example provides an electrode patch and a wearable electrochemical sensor for resisting sebum contamination in sweat detection. The preparation method is the same as that of Example 1, except that the working electrode of this example is a Ni-HHTP electrode. The preparation process of the working electrode in step 4 is as follows: Step 4-1, HHTP (0.015 mmol) and Ni(CH3COO)2·4H2O (0.25 mmol) were dissolved in 1.5 mL of a mixed solution (DMF: water = 1:7), and the Ni-HHTP precursor solution was obtained after ultrasonic treatment for 10 minutes; Step 4-2: Use inkjet printing technology to spray the Ni-HHTP precursor solution obtained in step 4-1 onto the gold layer, place it in an oven at 50°C for in-situ growth for 3 hours, wash it with water and acetone in turn, and then dry it to obtain a Ni-HHTP electrode (structure as shown in FIG. Figure 2 as shown).
[0027] Example 3 This example provides an electrode patch and a wearable electrochemical sensor for resisting sebum contamination in sweat detection. The preparation method is the same as that of Example 1, except that the working electrode of this example is a Cu-THQ electrode. The preparation process of the working electrode in step 4 is as follows: Step 4-1, dissolve Cu(NO3)2·3H2O (0.24 mmol) and ammonium acetate (2.4 mmol) in 1.8 mL of deoxygenated water, then add THQ (0.12 mmol) to the mixture, and obtain a Cu-THQ precursor solution after ultrasonic treatment for 10 minutes; Step 4-2: Use inkjet printing technology to spray the Cu-THQ precursor solution obtained in step 4-1 onto the gold layer, place it in an oven at 85°C for in-situ growth for 3 hours, wash it with water and acetone in turn, and then dry it to obtain a Cu-THQ electrode (structure as shown in Figure 2 as shown).
[0028] Example 4 This example provides an electrode patch and a wearable electrochemical sensor for resisting sebum contamination in sweat detection. The preparation method is the same as that of Example 1, except that the working electrode of this example is a hydrophobic Cu-HHTP / OTS electrode. The preparation process of the working electrode in step 4 is as follows: Step 4-1, HHTP (0.023 mmol) and Cu(NO3)2·3H2O (0.02 mmol) were dissolved in 4 mL of a mixed solution (DMF: water = 1:7), and the Cu-HHTP precursor solution was obtained after ultrasonic treatment for 10 minutes; Step 4-2, using inkjet printing technology to spray the Cu-HHTP precursor solution obtained in step 4-1 onto the gold layer, placing it in an oven at 60° C. for in-situ growth for 1 hour, washing it with water and acetone in turn, and then drying it to obtain a Cu-HHTP working electrode; Step 4-3, place the Cu-HHTP working electrode prepared in step 4-2 into a culture dish, place it in a vacuum oven and dry it at 90°C for 120 minutes to ensure that the sample is completely dried and then cooled; when the temperature drops to 50°C, add a small amount of OTS to the culture dish, and then put it back into the vacuum oven and dry it at 120°C for 120 minutes. When the oven temperature reaches 50°C, take out the Cu-HHTP electrode, then use n-hexane, ethanol and isopropanol for ultrasonic cleaning in sequence, and then vacuum dry it at room temperature overnight to obtain a Cu-HHTP / OTS electrode (structure as shown in Figure 2 as shown).
[0029] Example 5 This example provides an electrode patch and a wearable electrochemical sensor for resisting sebum contamination in sweat detection. The preparation method is the same as that of Example 1, except that the working electrode of this example is a ZIF-8 electrode. The preparation process of the working electrode in step 4 is as follows: Step 4-1, dissolve 2-methylimidazole (80 mmol) and zinc acetate (10 mmol) in 1 mL of water, and ultrasonicate for 10 minutes to obtain a ZIF-8 precursor solution; Step 4-2: Use inkjet printing technology to spray the ZIF-8 precursor solution obtained in step 4-1 onto the gold layer, place it in an oven at 60°C for in-situ growth for 1 hour, wash it with water and acetone in turn, and then dry it to obtain a ZIF-8 electrode (structure as shown in FIG. Figure 2 as shown).
[0030] Test Example 1 The contact angle of liquid (water or oil) on the surface of different MOFs electrode patches is evaluated by using a contact angle meter to measure the wetting performance of the liquid (water or oil) on the material surface. The specific test method is as follows: First, the MOFs electrode patch prepared in Examples 1-5 was placed flat on a measuring table; then, a fixed volume of water droplets were squeezed onto the electrode surface using a syringe, and the angle formed by the water droplets on the electrode surface was measured; for the contact angle of underwater oil, the electrode was placed below the water surface and a fixed volume of oil droplets were used for measurement. The water contact angle and underwater oil contact angle of different MOFs electrode patch surfaces in Examples 1-5 are shown in Figure 1. Figure 3 As shown by Figure 3 It can be seen that the MOFs materials of Examples 1-3 have smaller water contact angles and larger underwater oil phase contact angles, showing hydrophilicity and oleophobicity, while the MOFs materials of Examples 4-5 have larger water contact angles and smaller underwater oil phase contact angles, showing hydrophobicity and oleophilicity.
[0031] Test Example 2 A surface tension meter was used to test the sebum adhesion on the surfaces of different MOFs electrode patches. The specific test method is as follows: First, the wet MOFs electrode prepared in Examples 1-5 was placed in the inner cavity of the surface tension instrument and the hatch was closed. Then, a 2 uL drop of sebum was hung on the ring; finally, the ring was lowered to contact the electrode surface, and the instrument gave an adhesion value. The sebum adhesion test results of the MOFs electrode patches with different hydrophilicity are shown in Figure 2. Figure 4 As shown, it can be concluded that the sebum adhesion of Examples 1-3 is lower than that of Examples 4-5, especially the sebum adhesion of Example 1 is lower.
[0032] Test Example 3 The simulated sweat flow system combined with real-time electrochemical testing was used to evaluate the effect of sebum on the electrochemical signal stability of different MOFs electrode patches. The specific operation method is as follows: A constant-current injection pump was used to simulate the flow of sweat secreted by sweat glands and lipids secreted by sebaceous glands on the surface of the patch. Artificial lipids and artificial sweat were mixed at a volume ratio of 1:10 to form an emulsion, which was then transferred to the microfluidic channel of the electrode patch at a simulated flow rate of 0.5 mL / h (15.26 mg / cm² / min). At the same time, the current signal changes of different MOFs electrodes were continuously recorded.
[0033] Effect of sebum on the electrochemical signal stability of different MOFs electrode patches Figure 5 As shown, the current signals of the MOFs electrodes of Examples 1-3 are relatively stable, and the trend of change over time is not obvious, especially in Example 1, where the current ratio can be stabilized to 98%. The current signals of the MOFs electrodes of Examples 4-5 are unstable, and the trend of change over time is more obvious, especially in Example 5, where the current ratio drops from 100% to 27%.
[0034] Test Example 4 The accuracy and durability of the UA level in actual sweat samples were tested using the wearable electrochemical sensor integrated in the present invention. The specific testing method is as follows: First, the subjects were asked to fast overnight, and then the electrode patches of Example 1 (superhydrophilic Cu-HHTP sensor) and Example 5 (hydrophobic ZIF-8 sensor) were attached to the forehead of the subjects to test the uric acid level. 15 minutes after the start of the test, high-purine food and alcohol were consumed, and the UA level in the subjects' sweat was monitored and recorded every 1 hour. At the same time, the ELISA test kit was used to evaluate the actual level of UA in sweat at different times as a reference group, such as Figure 6 shown.
[0035] The results show that the detection accuracy of the hydrophobic ZIF-8 sensor of Example 5 is greatly affected by sebum, which can cause a significant passivation of the sensor performance, while the superhydrophilic Cu-HHTP sensor of Example 1 can accurately reflect the UA level in individual sweat and maintain long-term durability and sensitivity.
[0036] In view of this, the use of superhydrophilic MOFs electrodes proposed in the present invention can effectively solve the problem of sensor passivation caused by sebum biocontamination. This direct contact anti-biofouling electrode construction strategy achieves high sensitivity and high accuracy of wearable sweat sensor detection, enables continuous long-term monitoring, has good stability and long service life.
[0037] For those skilled in the art, the invention is not limited to the details of the above exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic characteristics of the invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the invention is defined by the appended claims rather than the above description, so it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any reference numerals in the claims should not be regarded as limiting the claims involved.
[0038] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any minor modifications, equivalent substitutions and improvements made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.
Claims
1. An electrode patch for resisting sebum contamination in sweat detection, comprising a working electrode, an Ag / AgCl@PVB reference electrode, an Au counter electrode and a flexible polyimide substrate, characterized in that: The working electrode is a super-hydrophilic MOFs sensing electrode, and the MOFs sensing electrode is prepared from any one MOFs precursor material of Cu-HHTP, Ni-HHTP, and Cu-THQ.
2. The electrode patch for resisting sebum contamination in sweat detection according to claim 1, characterized in that: The MOFs sensing electrode is prepared by spraying a MOFs precursor solution and an in-situ self-assembly process; the spraying method of the MOFs precursor solution includes any one of inkjet printing, dispensing, and dripping; the temperature of the in-situ self-assembly process is 50-85°C and the time is 0.5-3h.
3. The electrode patch for resisting sebum contamination in sweat detection according to claim 1, characterized in that: The Au counter electrode is prepared by a magnetron sputtering process, and the Ag / AgCl@PVB reference electrode is prepared by coating an Ag / AgCl suspension and dripping a PVB mixed solution; wherein the PVB mixed solution includes PVB, NaCl, F127 and methanol.
4. A wearable electrochemical sensor based on the electrode patch for resisting sebum contamination in sweat detection according to claim 1, characterized in that: It also includes a microfluidic sweat collection channel, which is in direct contact with the electrode patch.
5. The wearable electrochemical sensor according to claim 4, characterized in that: The microfluidic sweat collection channel comprises a PDMS microfluidic chip, and the PDMS microfluidic chip comprises a plurality of sweat inlets, a sweat storage area and a sweat outlet.
6. The wearable electrochemical sensor according to claim 5, characterized in that The PDMS microfluidic chip also includes an electrical stimulation gel, which includes an anode gel and a cathode gel, wherein the anode gel is prepared from agarose and carbachol, and the cathode gel is prepared from agarose and NaCl.
7. The wearable electrochemical sensor according to any one of claims 4 to 6, characterized in that: It also includes PI film substrate, flexible printed circuit board and APP software client.
8. The wearable electrochemical sensor according to claim 7, characterized in that The electrochemical sensor is integrated by an electrode patch, a PI film substrate, a microfluidic sweat collection channel, a flexible printed circuit board and an APP software client, wherein the electrode patch is located between the PI film substrate and the microfluidic sweat collection channel, and the microfluidic sweat collection channel is located on the flexible printed circuit board.
9. The wearable electrochemical sensor according to claim 5, characterized in that: The preparation of the PDMS microfluidic chip includes a photolithography process and a PDMS chip inverting process. The photoresist used in the photolithography process is SU-8, the coating speed is 1800-2000 rpm, the coating time is 30-45 s, and the thickness of the obtained photoresist layer is about 100-120 um.
10. The wearable electrochemical sensor according to claim 9, characterized in that: The photolithography process also includes an exposure process and a development process, and the exposure dose in the exposure process is 230-250mj / cm 2 , the baking temperature is 85-100°C; the developing time of the developing process is 7-10min, and the baking temperature is 130-140°C.
Citation Information
Patent Citations
Flexible sweat multi-marker electrochemical sensor based on metal organic framework derivative and application of flexible sweat multi-marker electrochemical sensor
CN114813868A
Wearable patch for animal heat stress detection and preparation method
CN117883077A
Wearable multi-channel sweat sensing patch based on MOFs (Metal-Organic Frameworks) electrode as well as preparation method and application of wearable multi-channel sweat sensing patch
CN118533924A
Sweat sensing device kidney biomarker measurement
US20200077936A1
Formation of metal-organic frameworks
US20210230191A1